Review of the State of the Art on Self-Management, Sustainability, and Continuity of Dance Festivals in Bogota (The Voz a Vos Bulletin, 2025)
This article establishes the categories of economy, culture, and independent dance festivals. These dimensions constitute the theoretical and conceptual focus. A mixed methodology (qualitative and quantitative) is used to conduct the study. This allows for the initial review and analysis of literature, revealing other topics such as territory, creative districts, cultural goods and services, and the creative economy, which are relevant to the research.Likewise, this document presents the initial results of the implementation of an instrument that provides guidelines for the design of organizational, systematization, and documentation mechanisms to help mitigate the sustainability issues faced by many of Bogotá's independent festivals.Initial findings corroborate the importance of analysis and the execution of studies that establish the concordance and articulation between economy, culture, and independent festivals, promoting strategies that enable self-management and sustainability.
Keywords: Dance; Public Policy; Creative District; Festivals; Economic Sustainability; Culture